Land occupation patterns and microclimates in the Brazilian continental tropical region: correlations and an indicator proposal - Duarte, Denise Helena Silva (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
This paper is concerned with the urban microclimate in the Brazilian continental tropical climate region. The purpose is to measure correlations between air temperature and some parameters of land occupation in the region, using urban planning variables that can be controlled by municipal regulation, showing distinct urban climatic phenomena for day and night periods. Considering the existing correlations, this research work suggests an indicator relating building density, area covered by trees, and water surface in urban areas, in order to guide the necessary procedures to ameliorate the harsh urban climate in the region.